2016
DOI: 10.1128/jb.00908-15
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Germination Phenotypes of Several Clostridium difficile Strains Suggests Another Role for the CspC Germinant Receptor

Abstract: Clostridium difficile spore germination is essential for colonization and disease. The signals that initiate C. difficile spore germination are a combination of taurocholic acid (a bile acid) and glycine. Interestingly, the chenodeoxycholic acid class (CDCA) bile acids competitively inhibit taurocholic acid-mediated germination, suggesting that compounds that inhibit spore germination could be developed into drugs that prophylactically prevent C. difficile infection or reduce recurring disease. However, a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 61 publications
3
62
1
Order By: Relevance
“…Some C. difficile strains are more primed to germinate in response to the taurocholic acid germinant than others (91). However, these differences do not appear to be linked to differences in the CspBA or CspC protein sequences, because any differences in protein sequence were ribotype specific, but the observed differences in germination were not (91).…”
Section: Csp-type Germinant Receptorsmentioning
confidence: 73%
“…Some C. difficile strains are more primed to germinate in response to the taurocholic acid germinant than others (91). However, these differences do not appear to be linked to differences in the CspBA or CspC protein sequences, because any differences in protein sequence were ribotype specific, but the observed differences in germination were not (91).…”
Section: Csp-type Germinant Receptorsmentioning
confidence: 73%
“…31,32 Given this, we examined the sequences of CspC, from R20291, an epidemic strain that is not inhibited by CamSA and 630, a nonepidemic strain that is inhibited by CamSA with an IC 50 of 58 μM. To our surprise, we found that the sequences were 99.3% conserved between both strains.…”
Section: Resultsmentioning
confidence: 95%
“…Bile acid signatures in the host GI tract have a significant influence upon the pathogenesis of C. difficile . Bile acids (in particular TCA) in the small intestine play a role in triggering the germination of spores into vegetative cells, while other bile acids (CDCA) inhibit this process [37,38] . Subsequently, the presence of secondary bile acids in the colon appears to be a major factor that influences host resistance to infection [9,10] .…”
Section: Difficile Infectionmentioning
confidence: 99%